Stress Coping Strategies among College Students: A Case in the College of Education, Eritrea Institute of Technology - Yikealo, Dawit; Tareke, Werede (Open Science Journal, 2018)
The study was intended to investigate the stress coping strategies among College of Education (CoE) students in Eritrea Institute of Technology, Mainefhi. To investigate the students’ stress coping strategies, descriptive research was carried out among a total of 123 students participants who were randomly drawn from the CoE. A self-developed College Students Coping Strategies Scale which entails 15 items has been utilized. The results of the study presented that the students were found to use more positive stress coping strategies than the negative ones. An independent-sample t-test result indicated that there is no statistically significant relationship between gender and both positive and negative stress coping strategies. The study is expected to have an impact on broadening the horizon of knowledge and understanding of stress coping strategies practiced by the CoE students. The study will support the college students to identify the positive and negative coping strategies, thereby stick to the healthy ones.